Continuous Improvement Implementation in the Nottingham University Hospitals NHS Trust: A Case Study of a Continuous Improvement Programme & Project - Velzen, Jeena (2012)
This paper aims at identifying the extent to which the Nottingham University Hospitals NHS Trust has fulfilled literature requirements for successful continuous improvement as exemplified by its Better for You programme and chemotherapy service improvement project. Both the theory and ideals of the continuous improvement programme, along with the actualization of these philosophies and methodologies in the context of the particular project,were compared against a framework for the enabling success criteria for continuous improvement implementation.